IFITM3 clusters on virus containing endosomes and lysosomes early in the influenza: a infection of human airway epithelial cells - Kummer, Susann; Avinoam, Ori; Kräusslich, Hans-Georg (Viruses, 2019)
Interferon-induced transmembrane proteins (IFITMs) have been shown to strongly affect influenza A virus (IAV) infectivity in tissue culture. Moreover, polymorphisms in IFITM3 have been associated with the severity of the disease in humans. IFITM3 appears to act early in the infection, but its mechanism of action and potential interactions with incoming IAV structures are not yet defined. Here, we visualized endogenous IFITM3 interactions with IAV in the human lung epithelial cell line A549 and in primary human airway epithelial cells employing stimulated emission depletion super-resolution microscopy. By applying an iterative approach for the cluster definition and computational cluster analysis, we found that IFITM3 reorganizes into clusters as IAV infection progresses. IFITM3 cluster formation started at 2-3 h post infection and increased over time to finally coat IAV-containing endosomal vesicles. This IAV-induced phenotype was due to the endosomal recruitment of IFITM3 rather than to an overall increase in the IFITM3 abundance. While the IAV-induced IFITM3 clustering and localization to endosomal vesicles was comparable in primary human airway epithelial cells and the human lung epithelial cell line A549, the endogenous IFITM3 signal was higher in primary cells. Moreover, we observed IFITM3 signals adjacent to IAV-containing recycling endosomes.
Gesehen am 06.04.2020